2003
DOI: 10.1309/q2hxbq174a1r8h5y
|View full text |Cite
|
Sign up to set email alerts
|

Interinstitutional Pathology Consultations

Abstract: We retrospectively determined the clinical impact of 1,000 randomly selected interinstitutional pathology consultations (IPCs). An IPC included all specimens from the patient. IPCs were classified as concordant or discordant with the original diagnosis. Discordant IPCs were classified as having a clinical impact or no impact. Discordant IPCs owing to interpretation differences were subclassified further. The IPCs included 1,522 specimens (1,204 histology, 318 cytology); 923 (92.3%) were concordant, 9 (0.9%) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…A review performed at the only cancer centre in Taiwan observed major discordance in 6% of mandatory interinstitutional pathology consultations 5 . Weir et al at the University Health Network in Toronto observed a 6.8% discordance rate in 1000 randomly selected consultations 4 . In both the Iowa City and Toronto studies, approximately half the discordant findings had clinical impact.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A review performed at the only cancer centre in Taiwan observed major discordance in 6% of mandatory interinstitutional pathology consultations 5 . Weir et al at the University Health Network in Toronto observed a 6.8% discordance rate in 1000 randomly selected consultations 4 . In both the Iowa City and Toronto studies, approximately half the discordant findings had clinical impact.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, however, inter-institutional pathology consultation is variably applied 11,12 . Suggested reasons for variability in the adoption of routine second-opinion pathology include workload constraints 5 , financial costs 6 , uncertainty about the value of reviews, and concerns about treatment delay 4 . Our institution had a policy of routine review upon referral in all cases of breast cancer patients with original pathology reported at an outside institution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations